ANALISIS IMLEMENTASI PP NO 43 TAHUN 2004 TENTANG PELAKSANAAN UPAYA PENINGKATAN KESEJAHTERAAN SOSIAL LANJUT USIA DI KOTA BATAM - Gheta Novelia; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study in the wake increasing human life expectancy to the number of elderly continues to increase but not accompanied by an increase in social welfare service various fields for the elderly, as a result many elderly need based on government regulation number 43 of 2004 has not been fulfilled so many elderly has problem in the implementation of the social function and cannot life decent and dignified life in. the formulation of the problem for this study is how the implementation of government regulation Number 43 of 2004 concerning in the implementation of effort to instruct social welfare for elderly in the Batam City? This study aims to determine the implementation of effort to improve the social welfare of the elderly in the Batam City based on government regulation number 43 of 2004. Sampling technique using purposive sampling with the number of respondent 45 persons, consisting of 2 employees of social service and cemetery in Batam, 3 nursing home manager, 20 elderly persons from nursing home and 20 elderly persons non nursing home. These data were collected through questioner, interview and observation technique. Data were analyses using descriptive quantitative. Based on the research that the author get, conclude that the implementation of government regulation Number 43 of 2004 concerning in the implementation of effort to instruct social welfare for elderly in the Batam City being in the unfavorable category, the percentage gains in the unfavorable category by 64% and in good category by 36%.Keyword: Implementation, Government Regulation, Welfare, Elderly